Investigation of food safety perceptions, practices, and workplace policies among employees of pet and animal feed stores that sell and do not sell raw meat-based diets - Lord, Jennifer; Cozzarelli, Marie; Lyon, Sara; Pugh, Sheri; Thompson, Sharon R. (Frontiers in Veterinary Science, 2025)
BackgroundPet and animal feed store employees face numerous occupational health hazards, including exposure to pathogens from handling contaminated animal food products. This study aimed to (1) investigate knowledge, sanitation practices, and workplace policies related to handling animal food and treats among employees of pet food and animal feed retailers in the United States (US) and (2) determine whether differences exist between employees of stores that sell raw pet food products and those that do not.MethodsA survey evaluating sanitation practices, training, and knowledge of disease risk related to animal husbandry and food handling was distributed to pet and animal feed store employees across the US by the University of Tennessee Center for Agriculture and Food Security and Preparedness (CAFSP), part of the Tennessee Integrated Food Safety Center of Excellence. Pet and feed stores that were contacted for participation were identified by searching for stores that posted their email addresses online. Student workers and CAFSP contractors helped to identify pet and feed stores in their area and distribute surveys, which were disseminated via email, mail, and hand-delivery. Chi-square tests and Wilcoxon rank sum tests were used to assess differences between employees of stores that sold raw pet food and those that did not.ResultsTwo hundred and six surveys were completed by employees of pet and animal feed stores in the 15 states, located in the Southeast, Midwest, Southwest, and Western US. Overall, just 25.3% (95% CI, 19.7, 31.7%) of respondents had received training on disease risk related to handling animal food. Compared to employees of stores that did not sell raw food, those who worked at raw food retailers had significantly higher perceived risk of illness (p = 0.0360). They tended to report more frequent surface disinfection (p = 0.0054), but not handwashing (p = 0.0542) than those who did not sell raw food. There were no significant differences in general workplace handwashing policies (p = 0.7800) or those specifically related to handling animal food (p = 0.0517). A substantial percentage of employees of both raw food retailers (41.5%) and those that did not sell raw food (67.8%) either rarely or never provided customers with food safety information.ConclusionFindings of this study indicate a need for ongoing training and outreach regarding food safety practices and zoonotic and foodborne disease risk among animal feed store employees. Stores should implement clear workplace hygiene policies and expand employee training and customer education to improve food safety standards and minimize disease risks.